ChemInform Abstract: Development and Applications of Highly Selective Palladium‐Catalyzed Monocoupling Reactions of (Cyclo)alkenes and 1, 3‐Alkadienes Bearing Two or Three Electrophilic Sites and Bis(enol triflates) with Terminal Alkynes. Issue 44 (14th October 2013) - Rossi, Renzo; Bellina, Fabio; Lessi, Marco; Manzini, Chiara
Abstract Review: < 250 refs.